2016
DOI: 10.1007/s40473-016-0077-2
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise in People with Schizophrenia: Neural and Neurocognitive Benefits

Abstract: Schizophrenia is characterized by extensive neurocognitive deficits, which are linked to greater disability, poorer functional outcome, and have been suggested to impact daily functioning more than clinical symptoms. Aerobic exercise (AE) has emerged as a potential intervention. This review examines the impact of AE on brain structure and function along with neurocognitive performance in individuals with schizophrenia. Preliminary evidence indicates that AE can increase hippocampal volume and cortical thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 105 publications
0
28
0
Order By: Relevance
“…Some previous studies found the protective effect of clozapine on all‐cause mortality after adjustment of baseline history of cardiovascular disease including ischaemic heart disease . However, after clozapine initiation, the likelihood of having cardiometabolic illnesses such as hypertension, diabetes mellitus and hyperlipidaemia may increase . Because of the cardiovascular adverse effects of the drug, it is possible that clinicians may more strongly advise smoking cessation to clozapine users, with this leading to reduced smoking behaviour .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous studies found the protective effect of clozapine on all‐cause mortality after adjustment of baseline history of cardiovascular disease including ischaemic heart disease . However, after clozapine initiation, the likelihood of having cardiometabolic illnesses such as hypertension, diabetes mellitus and hyperlipidaemia may increase . Because of the cardiovascular adverse effects of the drug, it is possible that clinicians may more strongly advise smoking cessation to clozapine users, with this leading to reduced smoking behaviour .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients who meet the definition of treatment resistance may be biologically distinct from those with treatment‐responsive schizophrenia . In line with this, two recent studies have investigated the effect of clozapine use on mortality in TRS . The study using United States Medicaid data reported no significant mortality difference between those patients treated with clozapine and those without , whereas the Danish national registry study found an approximately twofold higher mortality in non‐clozapine users .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise is a promising new area of intervention for individuals across many stages of psychosis, including for those at clinical high risk for psychosis (CHR). [1][2][3][4][5][6][7][8] Despite the benefits of this new area of intervention, substantially less work has examined unique factors of the CHR population that would have bearing on tailoring an effective, early intervention (i.e., understanding characteristic health and starting fitness levels). 7,[9][10][11] Extant research, however, has relied solely on self-report measures of physical activity to assess fitness, 9,10,[12][13][14] with few exceptions.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has demonstrated that exercise interventions are effective in improving cognitive function 1,4,5,11,19 and neurological function 2,11 for individuals across the psychosis spectrum including, risk mental states, CHR, the first episode of psychosis, and schizophrenia populations. Although existing psychosis literature has established that individuals with psychosis have significantly poorer physical health, 1,6,14,19,20 the evidence regarding the physiological health of individuals at CHR for psychosis is unclear.…”
Section: Introductionmentioning
confidence: 99%